Influence of Anastomotic Leak After Elective Colorectal Cancer Resection on Survival and Local Recurrence: A Propensity Score Analysis. Issue 3 (March 2019) - Zimmermann, Markus S.; Wellner, Ulrich; Laubert, Tilman; Ellebrecht, David B.; Bruch, Hans-Peter; Keck, Tobias; Schlöricke, Erik; Benecke, Claudia R.
Abstract : BACKGROUND: The occurrence of anastomotic leakage is still a life-threatening complication for patients after colorectal surgery. In literature not only an impact on the short-term outcome but also on long-term survival and local recurrence of colorectal cancer patients is discussed. OBJECTIVE: This study aimed to investigate the impact of anastomotic leakage on long-term survival and local recurrence. DESIGN: A total of 1122 patients with resections for colorectal cancer were analyzed. In 94 patients (8.4%) there was clinical proof of anastomotic leakage. A reference group was defined as the 1028 patients without anastomotic leakage using 1:1 propensity score-matching according to the following criteria: age, sex, International Union Against Cancer stage, Karnofsky index, tumor site, and grading, as well as adjuvant chemotherapy. A calculation of overall survival, disease-free survival, and local recurrence rate was performed for both groups. SETTINGS: The study was conducted using a retrospective matched-pairs analysis, based on a prospectively maintained institutional colorectal cancer database. PATIENTS: Ninety-four patients with anastomotic leakage and 94 matched control subjects from a total of 1122 patients with resections for colorectal cancer were studied. MAIN OUTCOME MEASURES: Overall survival, disease-free survival, and local recurrence rate for patients with colorectal cancer with and without anastomotic leakage were measured. RESULTS: The propensity score matching successfully created 2 groups with no significant differences in the matching criteria. Survival analysis disclosed no significant differences between the groups in terms of overall survival, disease-free survival, and local recurrence rate. Univariate analysis identified age, Karnofsky index, International Union Against Cancer stage, and lymph node metastasis as significant prognostic factors. Multivariable analysis of these variates revealed age and positive lymph nodes as independent predictors of overall survival and disease-free survival. LIMITATIONS: The study was limited by nature of being a retrospective analysis and monocentric study. CONCLUSIONS: This matched-pairs analysis, comparing patients with colorectal cancer with and without anastomotic leakage, revealed no significant differences in overall survival, disease-free survival, and local recurrence rate. Contrary results in the literature might be caused by nonbalanced settings in nonmatched collectives. SeeVideo Abstract athttp://links.lww.com/DCR/A811 .